Controversies, implications and megalomania associated with the origins of the Yugoslav idea - Żurek, Piotr (Balcanica Posnaniensia. Acta et studia, 2009)
The aim of the article is to analyse the origins of the Yugoslav idea in the context of conflicting historiographical visions. In historiography, there has been confusion between the concepts of the ‘South Slavic idea’ and the ‘Yugoslav idea’, even though they refer to different political phenomena. The former encompasses a broad spectrum of national and expansionist programmes of the South Slavs, while the latter was a Croatian political concept from the second half of the 19th century. The article pays particular attention to the criticism of interpretations created by so-called pro-Yugoslav historians, who attributed a centuries-old tradition to Yugoslavism. Based on an analysis of documents written by 19th-century Croatian politicians identified with Yugoslavism and resolutions of the Croatian Sabor, the moment of birth and general characteristics of this trend are presented. The author argues that both overt actions (demands for the federalisation of the Habsburg monarchy) and covert actions (contacts with Serbia) were aimed at strengthening the position of Croats in relation to their political environment. Religious aspirations were also subordinated to this goal. The presentation of the Yugoslav idea as the common heritage of the South Slavs is the result of later propaganda and political efforts.